Medical significance of Caenorhabditis elegans. - Aboobaker, A; Blaxter, M (2000)
Caenorhabditis elegans is now the model organism of choice for a growing number of researchers. A combination of its apparent simplicity, exquisite genetics, the existence of a full molecular toolkit and a complete genome sequence makes it ideal for rapid and effective study of gene function. A survey of the C. elegans genome indicates that this 'simple' worm contains many genes with a high degree of similarity to human disease genes. For many human disease genes it has proven, and will continue to prove, difficult to elucidate their function by direct study. In such cases simpler model organisms may prove to be a more productive starting point. The basic function of a human disease gene may be studied in the background of C. elegans, in which the most important interactions are likely to be conserved, providing an insight into disease process in humans. Here we consider the significance of this modality for human disease processes and discuss how C. elegans may, in some cases, be ideal in the study of the function of human disease genes and act as a model for groups of parasitic nematodes that have a severe impact on world health.